NESATYS KAIP REDUKTYVISTINĖS PRIEŽASTINGUMO ANALIZĖS ARGUMENTAS. - Grenda, Vytautas (Problems / Problemos, 2008)
The article advances an argument in favour of the reductionist, Humean conception of causation. The author draws upon an insight of David Lewis and Hugh Mellor: there can be no irreducible relation between causes and their effects, because not only the case that something exists, but also the case that something does not exist (i. e. absence) can be called a cause or an effect. If there's no such a relation, then the thought experiments that are directed against the so-called "Humean supervenience" thesis cannot prove that causation is an irreducible feature of the world. The utmost such experiments can prove is that the ordinary conception of causation is inconsistent.